2020
DOI: 10.1155/2020/6194864
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chemokine (C–X–C Motif) Ligand 10 (CXCL10) in Renal Diseases

Abstract: Chemokine C–X–C ligand 10 (CXCL10), also known as interferon-γ-inducible protein 10 (IP-10), exerts biological function mainly through binding to its specific receptor, CXCR3. Studies have shown that renal resident mesangial cells, renal tubular epithelial cells, podocytes, endothelial cells, and infiltrating inflammatory cells express CXCL10 and CXCR3 under inflammatory conditions. In the last few years, strong experimental and clinical evidence has indicated that CXCL10 is involved in the development of rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 148 publications
1
32
0
Order By: Relevance
“…In normal condition, CXCL10 is expressed at low levels in the kidney, but their expression levels are upregulated in renal tubular cells after insult, involving in the pathogenesis of AKI [11,12,27]. Higher uCXCL10 levels were found among the critically ill children with AKI in our study, which was in consistent with a prospective nested case-control study performed by Ho J et al [17].…”
Section: Discussionsupporting
confidence: 91%
“…In normal condition, CXCL10 is expressed at low levels in the kidney, but their expression levels are upregulated in renal tubular cells after insult, involving in the pathogenesis of AKI [11,12,27]. Higher uCXCL10 levels were found among the critically ill children with AKI in our study, which was in consistent with a prospective nested case-control study performed by Ho J et al [17].…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, no other studies have been performed except our previous study on serum NGAL [ 43 ]. Therefore, we aimed to evaluate the diagnostic value of the serum concentrations of biomarkers whose urine concentrations have exhibited promising results for detection of VIKI (osteopontin, NGAL, clusterin) or other drug-induced kidney injury (TFF3) and those that have shown to reflect renal tubular injury (CXCL10, IL-18, TNF-R1, osteopontin, RBP4, and cystatin C) for the diagnosis of VIKI [ 37 , 39 , 44 ]. In our study, serum TFF3, cystatin C, TNF-R1, and osteopontin showed the best diagnostic value for VIKI.…”
Section: Discussionmentioning
confidence: 99%
“…Based on experimental animal model studies, VIKI is suggested to be associated with oxidative stress caused by reabsorbed vancomycin accumulated in the lysosomes of proximal tubular cells [ 12 , 35 , 36 ]. Therefore, the biomarkers shown to reflect tubular injury in previous publications were also evaluated, such as cystatin C, tumor necrosis factor receptor 1 (TNF-R1), interleukin-18 (IL-18), C-X-C motif chemokine ligand 10 (CXCL10), osteopontin, and retinol binding protein 4 (RBP4) [ 37 , 38 , 39 ]. Here, we aim to identify candidate serum biomarkers for the diagnosis of VIKI.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the anti-inflammatory and anti-fibrosis therapeutic efficacy, we evaluated the therapeutic effects of DXMS/CAP@PLGA-ILs in a mouse model of mesangial proliferative glomerulonephritis (MesPGN), the most common pathological form of GN, which is characterized by MC proliferation and mesangial matrix accumulation, and inflammation-related cytokines play an important role in its pathology. 30 , 31 Habu snake venom (HSV) was used to induce the mouse model of MesPGN. 32 , 33 To improve the success rate of modeling, HSV was injected twice through the caudal vein.…”
Section: Methodsmentioning
confidence: 99%